2016
DOI: 10.1039/c6gc01060a
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight bio furan-based co-polyesters for food packaging applications: synthesis, characterization and solid-state polymerization

Abstract: High molecular weight bio furan-based copolyesters have been synthesized by melt polycondensation and solid-state polymerization for packaging applications as bio based alternatives to PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 18 publications
6
91
0
Order By: Relevance
“…From PPF to PCF, with the increasing content of CHDM units, the T g monotonously increased from 56.5 °C for PPF to 79.8 °C for PCF. In previous literatures, CHDM was also taken to copolymerize with PEF and PBF. It was reported that the T g of PECFs would decrease with the increasing content of CHDM units .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From PPF to PCF, with the increasing content of CHDM units, the T g monotonously increased from 56.5 °C for PPF to 79.8 °C for PCF. In previous literatures, CHDM was also taken to copolymerize with PEF and PBF. It was reported that the T g of PECFs would decrease with the increasing content of CHDM units .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, modification of PEF and PBF with enhanced thermal and mechanical properties have been achieved by using 1,4‐cyclohexanedimethylene (CHDM), a primary diol with non‐planar six‐member ring as a comonomer . In the present study, CHDM was taken to polymerize with PDO and FDCA with the purpose to increase the thermal and mechanical properties of PPF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Recently,t he US Department of Energy( DOE), DuPont Industrial Bioscience, and Archer Daniels Midland Co. have declared FDCA as one of the most important valueadded chemicals, which has the potential to generate exciting high-performance renewable materials in the 21 st century. [25,26] Despite the potentiala pplication of FDCA-based polymers such as polyesters, [27] polyamides, [28] and epoxy resins [29] in the production of bioplastics, [30] 3D printing, [31] coatings in automotive and marine industries, [32] and in the fabrication of biomedical devices, [33] the environmentally friendly synthesis of bio-based polymers and advanced methods for the generationo fh ighmolecular-weight polymers have not been exploredc ompletely.M ost of the protocols reported for the synthesis of biobased polymers that display variousp hysical and chemical properties involveh arsh reaction conditions, metal catalysts, and intense purification steps. [25,26] Despite the potentiala pplication of FDCA-based polymers such as polyesters, [27] polyamides, [28] and epoxy resins [29] in the production of bioplastics, [30] 3D printing, [31] coatings in automotive and marine industries, [32] and in the fabrication of biomedical devices, [33] the environmentally friendly synthesis of bio-based polymers and advanced methods for the generationo fh ighmolecular-weight polymers have not been exploredc ompletely.M ost of the protocols reported for the synthesis of biobased polymers that display variousp hysical and chemical properties involveh arsh reaction conditions, metal catalysts, and intense purification steps.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an increasing interest in the investigation on the biomass having aromatic skeletons due to its rigid chemical structure that can endow the materials with high thermostability . The renewability and remarkable abundance of biomass have seen interest from the researchers in both academia and industry.…”
Section: Introductionmentioning
confidence: 99%